Factors Influencing the Performance of Women Entrepreneurs’ in Kathmandu - Nishad, Divya (Nepalese Journal of Finance, 2025)
This study examines the factors influencing the performance of women entrepreneurs’ in Kathmandu. Women entrepreneurs’ performance is the dependent variable. The selected independent variables are motivation, need for achievement, self-efficacy, locus of control and education. The study is based on the primary data with 130 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and factors influencing the performance of women entrepreneurs’ in Kathmandu. The study showed a positive impact of motivation on women entrepreneurs’ performance. It indicates higher the motivation higher will be women entrepreneurs’ performance. Likewise, need for achievement are positively correlated to women entrepreneurs’ performance. It indicates that higher need for achievement leads to increase women entrepreneurs’ performance. Similarly, self-efficacy is positively correlated to women entrepreneurs’ performance. It indicates that higher self-efficacy stimulates the women entrepreneurs’ performance. Moreover, locus of control are positively correlated to women entrepreneurs’ performance. It indicates that higher the locus of control higher will be the women entrepreneurs’ performance. In addition, education are positively correlated to women entrepreneurs’ performance. It indicates that educational background has positively contributed on women entrepreneurs’ performance.